STRATEGIC MARKETING TRANSFORMATION THROUGH BIG DATA UTILIZATION: IN- DEPTH ANALYSIS OF TRANSLATING GIGANTIC INFORMATION INTO DECISIONSINFLUENCING TACTICAL AND BUSINESS STRATEGIES - Ananta Budhi Danurdara; Anjani; Nenden Hendayani; Rahma Helal Al_ Jbour; Iyad Abdallah Al- Shreifeen (CV. Adiba Aisha Amira, 2025)
In today's data-driven landscape, the convergence of strategic marketing and Big Data catalyzes a transformative journey for organizations. This research, comprising a comprehensive analysis, explores the profound impact of Big Data on reshaping marketing strategies. Delving into the intricate dynamics of decision- making processes, the study elucidates how vast data sets influence tactical and business strategies. With an emphasis on translating gigantic information into actionable insights, the research unveils the symbiotic relationship between data- driven decision-making and organizational agility. The abstract underscores the pivotal role of Big Data in enhancing customer engagement, informing targeted promotions, and contributing to broader business objectives. A critical evaluation of existing literature identifies strengths and weaknesses in current studies, emphasizing the need for in-depth exploration into industry-specific contexts and ethical considerations. In considering future directions, the study anticipates a continued evolution toward more sophisticated analytics tools, including artificial intelligence and machine learning. The implications for businesses involve staying abreast of emerging trends, investing in advanced analytics capabilities, and addressing ethical considerations. This research contributes to a comprehensive understanding of leveraging Big Data for strategic marketing transformation, offering insights into the dynamic intersection of data-driven decision-making and organizational success.